Biomass-involved synthesis of N-substituted benzofuro[2, 3-d]pyrimidine-4-amines and biological evaluation as novel EGFR tyrosine kinase inhibitors. Issue 23 (26th May 2017) - Sheng, Jianfei; Liu, Zhihong; Yan, Ming; Zhang, Xuejing; Wang, Dejian; Xu, Jun; Zhang, Ensheng; Zou, Yong
Abstract : Facile synthesis of N -substituted benzofuro[2, 3- d ]pyrimidine-4-amines from shikimic acid and biological evaluation as novel EGFR TKIs is described. Abstract : Shikimic acid (1 ) is a renewable biomass which could be obtained sustainably through natural product isolation or metabolic engineering. Owing to its great potential in chemical conversion, the value-added utilization of this non-grain biomass has received much attention in recent years. Based on the established transformation route from shikimic acid (1 ) to methyl 3-dehydroshikimate (3-MDHS, 2 ) and to the multi-functionalized methyl 2-amino-3-cyanobenzofuran-5-carboxylate (3 ), we disclose a facile and transition metal-free method to access a series of N -substituted benzofuro[2, 3- d ]pyrimidine-4-amines in 63%–90% yields. The identification of these compounds as EGFR tyrosine kinase inhibitors has also been described. Among them, compound5h exhibited the most potent inhibitory effect against EGFR tyrosine kinase with an IC50 of 1.7 nM and excellent antiproliferative activity against A431 and A549 cell lines with a GI50 of 5.1 and 12.3 μM, respectively.